Feminisms : diversity, difference and multiplicity in contemporary film cultures - Mulvey, Laura; Backman Rogers, Anna (2015)
This collection brings together an exciting group of established and emerging scholars to consider the history of feminist film theory and new developments in the field and in film culture itself. Opening the field up to urgent questions and covering such topics as new experimental film, the digital image, consumerism, activism, and pornography, Feminisms will be essential reading for scholars of both film and feminism.